Hydrogeology Journal Official Journal of the International Association of Hydrogeologists - Voss, Clifford I.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Hydrogeology Journal has acquired a large worldwide readership since its inception in 1992. The Journal's emphasis is to: Foster understanding of hydrogeology, a practical discipline aimed at bettering the human situation on earth, Describe worldwide progress in hydrogeology, And to provide an inexpensive and widely accessible forum for scientists, researchers, engineers, and practitioners in developing and industrialized countries alike. A mainstream paper in Hydrogeology Journal integrates subsurface hydrology and geology with the other supporting disciplines (such as geochemistry, geophysics, geomorphology, geobiology, surface-water hydrology, tectonics, mathematics, numerical modeling, economics, and sociology) to explain phenomena observed in the field. Hydrogeology Journal publishes peer-reviewed papers in both theoretical and applied aspects of hydrogeologic science, including: Theoretical and field studies ranging in scale from local areas and short time periods to regional or global problems and geologic time, Techniques and innovative instrumentation in the laboratory and field (for example, hydrologic, geochemical, geophysical, and mathematical), Water-resource and related mineral-resource evaluations, Reports of observed hydrogeologic phenomena, Overviews of hydrogeologic systems of interest in various regions, State-of-the-art-reviews, Philosophy of scientific methods in hydrogeology, Interaction between populations and hydrogeologic systems, Economics of hydrogeologic systems, Ramifications of hydrogeology on both environmental protection and optimal employment of natural resources, And the history of hydrogeology and biographies of eminent hydrogeologists.
Keywords: Hydrology; Water quality; Water pollution; Geology; Geophysics; Hydrogeology; Hydrogeology; Hydrology/Water Resources; Geology; Water Quality/Water Pollution; Geophysics/Geodesy.; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution